Listeria monocytogenes virulence factor secretion: don't leave the cell without a chaperone - Cahoon, Laty A.; Freitag, Nancy E. (Frontiers in Cellular and Infection Microbiology, 2014)
In Gram-positive bacteria, the secretion of proteins requires translocation of polypeptides across the bacterial membrane into the highly charged environment of the membrane-cell wall interface. Here, proteins must be folded and often further delivered across the matrix of the cell wall. While many aspects of protein secretion have been well studied in Gram-negative bacteria which possess both an inner and outer membrane, generally less attention has been given to the mechanics of protein secretion across the single cell membrane of Gram-positive bacteria. In this review, we focus on the role of a post-translocation secretion chaperone in Listeria monocytogenes known as PrsA2, and compare what is known regarding PrsA2 with PrsA homologs in other Gram-positive bacteria. PrsA2 is a member of a family of membrane-associated lipoproteins that contribute to the folding and stability of secreted proteins as they cross the bacterial membrane. PrsA2 contributes to the integrity of the L. monocytogenes cell wall as well as swimming motility and bacterial resistance to osmotic stress; however its most critical role may be its requirement for L. monocytogenes virulence and viability within host cells. A better understanding of the role of PrsA2 and PrsA-like homologs will provide insight into the dynamics of protein folding and stability in Gram-positive bacteria and may result in new strategies for optimizing protein secretion as well as inhibiting the production of virulence factors.